Jamu Pawukon as a sustainable gastronomy product: Calendar-based herbal knowledge from Javanese manuscripts - Nugroho, Setyo Prasiyono; Linkasari, Clara; Damasdino, Fian; Sinangjoyo, Nikasius Jonet; Osman, Sharina; Istiraharsi, Yedna (PHINISI, 2026)
Jamu Pawukon is a traditional herbal beverage prepared based on the pawukon calendrical system, a traditional Javanese calendar rooted in cultural manuscripts. This study aims to examine Jamu Pawukon as a form of calendar-based herbal gastronomy and to analyze its potential as a culture-based wellness tourism attraction in Sidorejo Tourism Village, Kulon Progo Regency, Special Region of Yogyakarta, Indonesia. A qualitative research approach was employed, with data collected through participatory observation, in-depth interviews, and documentation. Informants were selected using purposive sampling and included local cultural practitioners, herbal drink formulators, and tourists. Data were analyzed using a folklore approach to trace the historical background, cultural values, and hereditary practices of Jamu Pawukon preparation. The findings reveal that Jamu Pawukon originates from Javanese manuscript-based knowledge, particularly the Serat Pawukon Kiai Jotirto, which serves as the foundation for determining individual wuku (birth week) and corresponding herbal formulations. This practice positions jamu not merely as a health beverage, but as a form of calendar-based herbal gastronomy that integrates therapeutic functions, cultural meanings, and local knowledge systems. In the context of tourism, Jamu Pawukon is developed into an educational wellness tourism package that emphasizes experiential and cultural engagement. This study contributes to gastronomic and tourism scholarship by conceptualizing calendar-based herbal gastronomy as a novel framework for integrating intangible cultural heritage into experiential wellness tourism development. The study highlights the significant role of Jamu Pawukon in cultural preservation, destination identity strengthening, and the development of local wisdom–based wellness tourism.